The Revised European Social Charter An Article by Article Commentary - Lukas, Karin (Edward Elgar Publishing, 2021)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. The online open access to the book The Revised European Social Charter. An article-by-article commentary has been made possible with the financial assistance of the Council of Europe. The views expressed herein can in no way be taken to reflect the official opinion of the Council of Europe. This detailed Commentary explores the boundaries of social rights at a European level through analysis of the Revised European Social Charter (RESC), the most comprehensive regional document on social rights. The Commentary considers the treaty as the counterpart of the European Convention on Human Rights, examining how it sets out fundamental rights in the social field. It focuses primarily on the rich jurisprudence developed by the Charter's monitoring body, the European Committee of Social Rights (ECSR).